Peran Manajemen Ekonomi Syariah Dalam Mengatasi Kemiskinan - Cattelya Putri Maharani; Nidya Fakhirah; Siti Nurhalimah; Ika Ajeng Febrianti; Yayat Suharyat (LPPM Politeknik Pratama, 2023)
Poverty is a condition where a person is deprived and cannot meet one's essential needs, if one's essential needs are not met then one's life will be disrupted. This failure is generally reflected in real as well as mentally, it can cause mediocre sensations in the person who experiences it. The government has observed that various aspects of life have been significantly affected by the symptoms and effects of poverty. However, poverty in Indonesia continues to increase, as evidenced by the Money Service Monetary Strategy Organization measuring the limit of people's needs, increasing 5.95 percent to Rp535,547 in September 2022. The urban poverty rate increased to 7.53 percent in March 2022. In addition, there are 12.36 percent more poor people living in rural areas. This research aims as a solution to overcome poverty in Islamic economic management, through zakat, infaq, and shadaqah, Islam promotes the cultural cultivation of each individual's role in improving the quality of life and the process of social unity. This study uses a qualitative approach and the process of analysis researchers understand and interpret the meaning of events, interactions, and behavior of subjects in certain situations from the perspective of researchers rather than statistical procedures. As well as additional information or materials that are expected to complete the results of research obtained from different libraries and sources. By implementing zakat, infaq, and sadaqah it is hoped that it can help reduce the poverty rate.